Economics of financial institutions and markets - Smith, Paul F. (Homewood, Ill. : R. D. Irwin, 1971)
This book is designed to integrate the basic factual and descriptive materials on financial institutions and markets into economic theory and to present an overall view of the financial system as it relates to the economic process. It attempts to introduce enough institutional material to give the reader an understanding of the structure and organization of the financial system without destroying the essential simplicity of the theoretical framework of the system. The book contains sixteen chapters in four major sections. The first section, which contains four chapters, is entitled "The Nature of Financial Decisions". The next section, "The Behavior of Financial Institutions," discusses financial intermediation and types of financial institutions. The third section, containing five chapters, describes the nature and structure of financial markets. These chapters are descriptive of primary markets, secondary markets, the money market, and competition and performance of these markets. term structure of rates and the open market operations of the Federal Reserve. The last section, "Financial Money Flows and Aggregate Economics," consists of five chapters dealing primarily with money flows, theories of interest, financial markets and the level of economic activity, and the economic role of secondary markets.
Includes bibliographical references and index.
rpm 23/04/2018
Loans
Keywords: Finance; Financial institutions